A North American and global survey of perfluoroalkyl substances in surface soils: Distribution patterns and mode of occurrence. (October 2016) - Rankin, Keegan; Mabury, Scott A.; Jenkins, Thomas M.; Washington, John W.
Abstract: The distribution of 32 per/polyfluoroalkyl substances (PFASs) in surface soils was determined at 62 locations representing all continents (North America n = 33, Europe n = 10, Asia n = 6, Africa n = 5, Australia n = 4, South America n = 3 and Antarctica n = 1) using ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) systems. Quantifiable levels of perfluoroalkyl carboxylates (PFCAs: PFHxA-PFTeDA) were observed in all samples with total concentrations ranging from 29 to 14, 300 pg/g (dry weight), while perfluoroalkane sulfonates (PFSAs: PFHxS, PFOS and PFDS) were detected in all samples but one, ranging from <LOQ-3270 pg/g, confirming the global distribution of PFASs in terrestrial settings. The geometric mean PFCA and PFSA concentrations were observed to be higher in the northern hemisphere (930 and 170 pg/g) compared to the southern hemisphere (190 and 33 pg/g). Perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) were the most commonly detected analytes at concentrations up to 2670 and 3100 pg/g, respectively. The sum of PFCA homologues of PFOA commonly were roughly twice the concentration of PFOA. The PFCA and PFSA congener profiles were similar amongst most locations, with a few principal-component statistical anomalies suggesting impact from nearby urban and point sources. The ratio of even to odd PFCAs was consistent with the atmospheric oxidation of fluorotelomer-based precursors previously observed in laboratory and environmental studies. Given the soils were collected from locations absent of direct human activity, these results suggest that the atmospheric long-range transport (LRT) of neutral PFASs followed by oxidation and deposition are a significant source of PFCAs and PFSAs to soils. Graphical abstract: Highlights: We report on 32 per/polyfluoroalkyl substances (PFASs) in background soils. Remote North American sites include Inuvik Canada, La Paz Mexico, Auke Bay Alaska. Global includes Antarctica, Mabira Uganda, Vehendi Estonia, Southern Cross Australia. Quantifiable concentrations of PFASs were detected in every soil sample. Perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) were most common.